Proceso atención de enfermería en paciente masculino 54 años de edad con absceso de pulmón derecho y de mediastino. - Estrada Segura, Genesis Lisbeth (2023)
Lung abscesses are a necrotic infection of the lung characterized by a cavitary lesion filled with pus by pyogenic germs, from which a purulent necrotic cavity is formed, followed by microbial infection in which aspiration is a common etiological focus. The most frequent clinical symptoms are fever, nocturnal hyperhidrosis, pleuritic pains, profuse purulent expectoration. Bacterial infections include anaerobes, mycobacteria, fungi, parasites and other bacteria: anaerobic streptococci, staphylococcus aureus, hence our focus on the work done involved the use of a nursing care process in a 54-year-old male patient with right lung abscess and mediastinum to provide timely care and special care to prevent complications or death. The nurse socializes and interacts with the patient to obtain relevant information and make the nursing diagnosis, it should be noted that nursing aims to promote care, help, empathy, safety and provide quality care and warmth to humanity. The nursing care process is a rational and systematic method of planning and providing services to the patient, family, and community.